Guidelines for the Prevention of Coronavirus Disease 2019 (COVID-19) with Saṃvara in Buddhism - Phra Palad Somphan (Journal of Buddhist Innovation Review, 2020)
Abstract The eruption of Covid-19 spreads the virus from animals to human, then human to human eventually. Within one month, the contamination spans globally and halts each and individual livings on earth into exclusive new normal. The physical contacts and the inhalation of the virus are the definite causes of contamination. The cases and the death rolls are paralleling in the upward manners. Some cases, the patients show no sign or symptom, while the senior patients and/or patients with health issue complication are prone to decease. The global outbreak is accountable for two million cases with 700,000 deaths. The World Health Organization declares state of health emergency due the virus, yet encourage and enforce the social distancing to tackle the virus outbreak. Saṃvara or conscience, the mindful feeling toward the views and actions as a guide to the rightness or wrongness, comprises 5 categories, Patimokha Saṃvara – Conscience in Respecting Rules of Living, Sati Saṃvara – Conscience in spending the daily life with mindfulness, Jhanna Saṃvara – Conscience in Wisdom, Kanti Saṃvara – Conscience in tolerating and being neutral and Viriya Saṃvara – Conscience in Perseverance. In order to be free from defilements, conscience (Saṃvara) is the mainstream of life conducts in Buddhism aiming for the uplifting of the quality of minds, doings and speeches. Saṃvara is also the collaboration of Mindfulness and Wisdom at the proportionate degree to understand the world. Once the Mindfulness and Wisdom gear our minds, doings and speeches, the outcome will appear as Kanti and Viriya, which is basically perceived as the Wisdom drives our actions and thoughts. Sati and Jhanna helps us contemplate the true meanings of essence of life, being the most important paradigm of thought process before our interaction through minds, doings and speeches.